Application-related properties of giant magnetostrictive thin films - Lim, SH; Kim, HJ; Na, SM; Suh, SJ (ELSEVIER, 2002)
In an effort to facilitate the utilization of giant magnetostrictive thin films in microdevices, application-related properties of these thin films, which include induced anisotropy. residual stress and corrosion properties, are investigated. A large induced anisotropy with an energy of 6 x 10(4) J m(3) is formed in field-sputtered amorphous Sm-Fe-B thin films. resulting in a large magnetostriction anisotropy. Two components of residual stress, intrinsic compressive stress and tensile stress due to the difference of the thermal expansion coefficients between the substrate and thin film, are identified. The variation of residual stress with fabrication parameter and annealing temperature, and its influence on mechanical bending and magnetic properties are examined. Better corrosion properties are observed in Sm-Fe thin films than in Tb-Fe. Corrosion properties of Tb-Fe thin films. however, are Much improved with the introduction of nitro-en to the thin films without deteriorating magnetostrictive properties. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: ANISOTROPY